PENGARUH VARIASI PENAMBAHAN FLY ASH & BENTONIT TERHADAP SIFAT PASIR CETAK DAN CACAT GASHOLES PADA HASIL PENGECORAN LOGAM ALUMINIUM - Faqih Bahrudin; Budi Harjanto; Herman Saputro (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2019)
The objectives of this study to describe: (1) The effect of adding fly ash and bentonite to the permeability of molding sand. (2) The effect of adding fly ash and bentonite to the moisture of molding sand. (3) The effect of adding fly ash and bentonite to gasholes defect on aluminium metal casting. This study is conducted at Polytechnic of Manufaktur Ceper, Klaten. The method that used is pre-experimental design which one-shot case study design. The compositions of the molding sand are varied is fly ash and bentonite. The Sample variations are divided into 4 types based on fly ash and bentonite concentration. The comparison of fly ash and bentonite concentration are: variation A are 0%:9%, variation B are 1%:8%, variation C are 2%:7%, and variation D are 3%:6%. The tests which is done in this study such as permeability test by using permeability tester, moisture test by using moisture tester, and gaholes defect test by using visual observation and calculation of gasholes defect.The results showed that: (1) The adding fly ash and bentonite can decreased the permeability values of molding sand. The lowest permeability values occur at variation D that is 85.34 cm3/min. (2) The adding fly ash and bentonite can decreased the moisture of molding sand. The lowest moisture values occur at variation D that is 5,26 %. (3) The adding fly ash and bentonite can improved the quality of castings. The results of castings at variation B which adding fly ash and bentonite has less gasholes defects compared with variation which no adding fly ash that is 3,15 cm3